Açaí meal on diet digestibility for commercial laying hens - Rufino, João Paulo Ferreira (2020)
This study aimed to evaluate açaí meal in diets for commercial laying hens on apparent nutrient digestibility and apparent metabolizable energy. A total of 72 Hissex White laying hens (52-wks-old) were distributed in a completely randomized design, where treatments consisted of a control diet and an experimental diet (25% açaí meal) with six replicates of six birds each. Data collected were subjected to polynomial regression at 5%. Differences (p < 0.05) were detected in digestibility of all evaluated nutrients. Hens fed diets with 25% açaí meal presented worse (p < 0.05) metabolization and use of energy content. It can be concluded that hens fed diets containing açaí meal presented better use of crude protein, non-fiber carbohydrates and mineral matter. However, there was worse use of dry matter, fiber carbohydrates and ether extract. This result directly affected the energy metabolism of the birds. The inclusion of açaí meal reduced the energy use.